Electrochemical Benzylic C(sp3)–H Amidation via Ritter-Type Reaction in the Absence of External Mediator and Oxidant - Chu, Qiao; Zhou, Yeqin; Ji, Ce; Liu, Ping; Sun, Peipei (Synthesis, 2023)
A straightforward method involving electrochemical Ritter-type amidation of alkylarenes in the absence of external mediator and oxidant is described. This direct benzylic C(sp3)–H amidation utilizes cheap CH3CN or other nitriles as the nitrogen source and trace amount of H2O in the solvent as the oxygen and hydrogen source. A wide range of alkylarenes were found to be compatible, providing a variety of N-benzyl-substituted amides in moderate to good yields.
Keywords: electrochemical oxidation; benzylic C(sp3)–H amidation; Ritter-type reaction; external mediator free; oxidant free; N-benzylamides